MULTIKULTURALISME DALAM PENDIDIKAN ISLAM: MEMBANGUN KESADARAN DAN TOLERANSI DALAM KEANEKARAGAMAN BUDAYA - Ahmad Jamal Rohman; Silva Eka Diani; Acep Rizki AlFathir; Rizal Mustaidz Billah (Yayasan Al-Afif, 2024)
Stereotypes, prejudice and discrimination often arise in the Islamic education environment, which can hinder students' personal development, social interactions and tolerance toward individuals and groups with diverse cultural backgrounds. The purpose of this study is to understand and analyze how Islamic education might increase tolerance and kesadaran toward religious observance. Using a kualitatif research methodology and a study of pustaka, this research concludes that Islamic education must emphasize adherence to the faith as a positive value in the classroom. A learning approach is needed that prioritizes awareness and tolerance of cultural diversity. Apart from that, efforts to prevent and deal with stereotypes, prejudice and discrimination in education also need to be carried out. This research makes an important contribution to developing Islamic education programs that are more inclusive and fair. The results provide recommendations for policy makers, educators, Students and the general public about the significance of fostering tolerance and knowledge of cultural variety in order to preserve social harmony and inclusivity.